Pustular psoriasis of intertriginous areas - Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Generalized pustular psoriasis is one of the most severe, potentially life-threatening forms of psoriasis. Drugs, infections and pregnancy are usually the trigger. Objective. The aim of the study was to present a case of intertriginous pustular psoriasis. Case report . A 28-year-old woman, suffering from common psoriasis since the age of 7 years, developed, during the puerperium, annular lesions of pustular psoriasis with characteristic, marginal scaling. The lesions were localized in the axillae, groins and in the breast folds, spreading at the periphery with evident central clearing. No general symptoms were present and the patient only complained of moderate skin burning. She was treated with cyclosporin and 0.1% methylprednisolone aceponate cream. Skin lesions cleared completely in one month. Conclusions . Intertriginous pustular psoriasis seems to be a distinct subtype of generalized pustular psoriasis.